PP27. ESTABLISHMENT OF A HAEMATOPOIETIC STEM-CELL BASED THERAPY FOR BRAIN TUMOURS IN PRE-CLINICAL MOUSE MODELS - Andreou, Dr Tereza (Neuro Oncol, 2017)
Brain tumours are one of the most aggressive forms of cancer with limited treatment options. Current treatment options include surgical resection of the main tumour mass, radiation and chemotherapy treatments. Surgical resection will inadvertently leave ~ 5 % of cancer cells within difficult anatomical locations in the brain, while radiation and chemotherapy treatments will often lead to unwanted systemic toxicities. In an attempt to minimise systemic toxicities, we aim to develop a targeted approach for the delivery of therapeutic agents using haematopoietic stem cells (HSCs) as cellular delivery vehicles. We first evaluated the suitability of HSCs as drug delivery vehicles for brain tumours in a syngeneic mouse model. Murine Sca1+ HSCs isolated from mouse bone marrow (BM) were transduced with the lentiviral vector pFUGW expressing green fluorescent protein (GFP) and transplanted into lethally irradiated C57BL/6J mice. This resulted in successful BM engraftment as confirmed by flow cytometry. Subsequently, brain tumours in these mice were generated by intracranial implantation of primary glioma cell lines (GL261 and CT-2A) to address primary brain tumours or the murine breast carcinoma cell line, EO771, to address breast cancer brain metastases. Our studies show that the progeny of GFP-tagged HSCs strongly infiltrated primary brain tumours and brain metastases, with the main immune cell infiltrating population being CD11b+/F4/80+ macrophages. To address the issue of targeted therapy delivery specifically to brain lesions, we sought to identify gene promoters whose activity is specifically upregulated in the HSC progeny that infiltrates brain tumours. Gene expression analysis identified 3 genes whose expression is specifically upregulated in brain tumour infiltrating macrophages as opposed to macrophages infiltrating other tissues, namely bone marrow and spleen. To validate promoter specificity in our mouse models, we generated promoter:reporter constructs to drive GFP expression downstream of these 3 identified promoters. To this end, C57BL/6J mice were lethally irradiated and reconstituted with genetically modified murine Sca1+ HSCs expressing GFP downstream of the 3 identified promoters. Following successful bone marrow reconstitution, we tested promoter specificity in mouse models of breast cancer brain metastases. Our results show that 2 of the promoters display specific activity in the brain as opposed to other tissues (blood, bone marrow, spleen, lungs, liver, heart), suggesting that HSC progenitors can drive delivery of therapeutics specifically to the brain downstream of these 2 promoters. We now plan to test the delivery of therapeutic agents downstream of these tissue-specific promoters. This study demonstrates a proof-of-concept for using HSCs as cellular delivery vehicles for the targeted delivery of therapeutics to the brain to overcome the blood-brain barrier and has potential for combination therapy approaches in the future.